EKSTRAKSI PEKTIN DARI LIMBAH KULIT PISANG KEPOK (Musa paradisiaca) MENGGUNAKAN PELARUT ASAM SITRAT - Lukman Azis (The Journal of Teknologi Pangan, 2020)
Pectin is water soluble fiber contained in the fruits such as lemon, apple and banana. Food Industry uses pectin for stabilizer and thickener. The aim of this research was to analyse the purity of pectin from Kepok banana peel waste extracted by using citric acid. Maceration is used to extract the pectin from Kepok banana peel powder. The research used Rancangan Acak Lengkap (RAL) with the factor of citric acid concentration 5, 10, 15 and 20%. Data analysis used was Analysis of Variant (ANOVA) in which the treatment showed significant different (p<0.05) was continued to DMRT test 5%. The result of pectin extraction from Kepok banana peel waste showed that pectin extracted by using citric acid 5% was highest of 19% whereas it was significantly different (p<0.05) compared to other concentrations; 10,15 and 20%. The higher number of purity analysis was from pectin with the concentration of citric acid 5% with purity of 78%. Extracted pectin is influenced by the concentration of citric acid.